Negative Impacts of Forest Fires on Ecological Balance and Environmental Sustainability: Case of Turkey - Bakirci, Muzaffer (Journal for Geography, 2010)
Forests are a vital element in the Earth’s ecological balance, economy, biodiversity, water resources and air purity. On the other hand, forests are confronted with various threats – one of them being fires. Its distinctive geographical features provide Turkey with rich plant diversity along with an imbalance in the dispersion of forested land. 27% of Turkey’s surface area is covered by forests, most of which are concentrated on the coastal lands and their hinterlands. 2.135 forest fires were recorded in Turkey in 2008, resulting in a loss of 29.749 ha of forest. Although this figure translates into a decrease of 25% in the number of fires, the amount of destroyed forestland increased by 155% with respect to the previous year. This paper questions the incendiary causes and negative effects of fires in the case of Turkey.
Keywords: ecological balance; environmental sustainability; forest fires; Turkey